Ownership Structure, Corporate Governance and Dividend Policy: Evidence from Indonesia - Malavia Mardani, R; ., Moeljadi; ., Sumiati; Khusniyah Indrawati, N (KnE Social Sciences, 2018)
The purpose of this study is to examine the relationship between ownership structure, corporate governance, and dividend policy. The sample in this study is a financial company listed on the Indonesia Stock Exchange in the period 2014–2016. The results showed that managerial ownership is positively related to dividend policy. Institutional ownership is negatively related to dividend policy. Board size is negatively related to dividend policy, while independent board is positively related to dividend policy. Keywords: managerial ownership, institutional ownership, board size, independent board